2019
DOI: 10.1038/s41467-019-12618-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying operational lifetimes for coal power plants under the Paris goals

Abstract: A rapid transition away from unabated coal use is essential to fulfilling the Paris climate goals. However, many countries are actively building and operating coal power plants. Here we use plant-level data to specify alternative trajectories for coal technologies in an integrated assessment model. We then quantify cost-effective retirement pathways for global and country-level coal fleets to limit long-term temperature change. We present our results using a decision-relevant metric: the operational lifetime l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 35 publications
3
110
0
Order By: Relevance
“…First, a rapid transition requires early retirement of substantial coal-generation capacity while canceling newly planned coal projects. 29 , 30 China has been canceling planned coal projects since 2016 due to overcapacity and air pollution concerns, and canceled more than 130 GW of planned coal projects in 2019 alone. 30 However, by the end of 2019, about 80% of China's coal capacity was built after 2000 ( Figure 2 ).…”
Section: Current Policies and Barriersmentioning
confidence: 99%
“…First, a rapid transition requires early retirement of substantial coal-generation capacity while canceling newly planned coal projects. 29 , 30 China has been canceling planned coal projects since 2016 due to overcapacity and air pollution concerns, and canceled more than 130 GW of planned coal projects in 2019 alone. 30 However, by the end of 2019, about 80% of China's coal capacity was built after 2000 ( Figure 2 ).…”
Section: Current Policies and Barriersmentioning
confidence: 99%
“…Note that as the estimation of stranded scale is quite sensitive to the FLH and technical lifetime (Cui et al 2019), we also included a sensitive analysis (see SI.3). The first analysis shows the results under 4000 and 3500 h of FLH, and the second analysis shows the results under 30 and 35 years of lifetime assumption.…”
Section: Estimated Scale Of Assets With Stranded Riskmentioning
confidence: 99%
“…Moreover, they pointed out the importance of the power sector in decarbonizing the energy system (Tong et al 2019). Cui et al compared the existing and planned coal-based power plant development with climate targets to demonstrate that the operational lifetime of existing coal plants should be reduced to 35 and 20 years to meet the 2°C and 1.5°C targets, respectively (Cui et al 2019). With a focus on the US, Lyer et al also found that coal power plants may face the risk of being prematurely retired by modeling the low-emission development strategy with the GCAM model (Iyer et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the feasibility of such drastic energy system changes, existing studies have pointed out transition risks, such as carbon lock-in, stranded investment, and premature retirement relative to the expected lifetime of fossil fuelrelated infrastructure (Campiglio et al 2018;Mercure et al 2018;Seto et al 2016). At the global scale, several studies using IAMs have indicated that the lack of short-term mitigation actions would lead to premature phase-out of coal power plants and stranding of fossil fuel assets, resulting in increased stranded investment in the energy supply sectors (Bertram et al 2015;Cui et al 2019;Johnson et al 2015). At the national level, Iyer et al (2017) explicitly focused on disruptive changes between the US NDC and MCS, and quantified stranded coal capacity by 2050 using the Global Change Assessment Model (GCAM).…”
Section: Introductionmentioning
confidence: 99%